The minimum wage: An effective means to regain the electorate's confidence? - Natalie Laub; René Kalweit (ZBW - Leibniz Information Centre for Economics, 2021)
This paper analyses whether the introduction of the minimum wage in Germany had an effect on the electorate's support for ruling parties. Estimations base on data from a large household survey and exploit regional differences in the bite of the minimum wage. The results show that in regions where the bite of the minimum wage was higher, the support for ruling parties significantly decreased in the year in which the minimum wage was introduced. Individuals with earnings just above the minimum wage mainly drive this result, which is robust to different model specifications.
Keywords: D72; J31; 330